A collaborative auto-ethnographic exploration of socially just practices by new academics in two South African higher education institutions - Collett, K.S.; von der Heyden, B.; Pott, R.W.M.; Stander, J. (South African Journal of Higher Education, 2018)
ABSTRACT Challenges experienced in the higher education context require new academics to engage with issues of social justice in their pedagogical practices. This article focuses on such challenges and how these are met by the authors, who are new academics from two higher education institutions in South Africa. Using a collaborative auto-ethnographic approach to analyse and interpret practices from different disciplines and higher education institutions, critical insights into ‘response-able pedagogies’ are highlighted. ‘Response-able pedagogies’ may be described as those which foreground attentiveness, responsibility, curiosity and capability, are used as a lens to examine the pedagogical practices of the authors, as new academics. This lens is useful in that it illuminates ethical dimensions of how a socially just pedagogy might be enacted in disparate South African higher education contexts. Issues of language, academic literacies, resources, employability, cultural diversity, large classes, and student abilities are reflected upon in relation to new academics’ engagement with socially just pedagogies. The paper is intended to be a useful resource specifically, but not exclusively for, new academics entering the field of higher education in South Africa.